P84 Co-polyimide/Nanocrystalline Cellulose (NCC)-based tubular carbon membrane: effect of drying times for carbon dioxide separation at elevated carbonization temperature - Norazlianie, Sazali; Wan Norharyati, Wan Salleh; K., Kadirgama (Universiti Teknologi Malaysia, 2018)
In this study, the effect of drying time on the performance of tubular carbon membrane was investigated. P84 co-polyimide blends with Nanocrystalline cellulose (NCC)-based carbon membrane supported on ceramic tube was fabricated through the dip-coating technique. This study aims to investigate the effect of various drying times (12 hours, 24 hours, 3 days and 7 days) on the carbon dioxide separation properties. The gas permeation test of the resultant tubular carbon membrane was determined by using pure gas of CO2 and N2. In order to enhance the membrane performance, final carbonization temperature was executed at 800oC in Argon environment with flow rate of 200 mL/min. From the results, it was found that the best drying times was within 24 hours and such membrane showed the highest CO2/N2 selectivity (66.32±2.18).